PEMBERDAYAAN IBU RUMAH TANGGA DALAM PENGOLAHAN SAMPAH - Kaseng, Ernawati Syahruddin (Indonesian Journal of Applied Geography, 2023)
This study aims to describe and analyze how the empowerment of housewives in waste processing in waste banks. This research uses qualitative methods with a descriptive approach. The number of informants in this study was 5 people determined using purposive sampling techniques with criteria 1) Involved and knowing the process of organizing the empowerment of housewives in waste processing at the Waste Bank, 2) Responsible for the implementation of empowering housewives in waste processing at the Waste Bank, 3) Willing to be the subject of research for researchers. The data collection techniques used in this study were observation, interview and documentation methods. Data analysis techniques include data reduction, data presentation, and conclusions. The results of this study show that the inhibiting factors for the implementation of housewife empowerment are the performance of administrators and facilities while the driving factors are government policies, motivation and budget funds.